Artificial Intelligence in educational contexts: ethical uses of information and digital literacy - López-Pulido, Alfonso; Sánchez Ramírez, José Manuel (Derecom. Derecho de la Comunicación y de Nuevas Tecnologías, 2025)
The proliferation of digital technologies, including Artificial Intelligence (AI), has transformed the way we access, process and share information. However, this mutation has also intensified problems such as misinformation, difficulties in verifying information and possible unethical uses of AI, especially in educational and academic research contexts, as well as the danger of diminishing students’ linguistic expression capabilities and their independent thinking. In this paper we explore how these dynamics affect education, the challenges that students and teachers must overcome, and strategies to mitigate these risks, highlighting digital literacy.